Conversion of oil palm frond biomass to graphitic carbon for high-performance supercapacitor application - Ullah, Mohammad; Rasidi, Roslan; Jose, Rajan; Izan Izwan, Misnon (IOP Publishing, 2025)
This study focused on converting the biomass from oil palm frond (OPF) to graphitic carbon without using any activation chemicals at a relatively lower temperature (450, 550, and 650° C) with a one-step calcination process. The physicochemical properties of the produced unwashed graphitic carbon (WGC) were investigated using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), field emission scanning electron microscopy with energy dispersive X-ray (FESEM-EDX), and Brunauer-Emmett-Teller (BET) studies. The characterization of the prepared sample showed the presence of a porous structure in the resultant WGC. The XRD analysis revealed a distinct peak corresponding to the graphitic structure at the (002) location. The optimized WGC-650 exhibited a specific surface area (SBET) of 305.87 m2 g−1, a pore diameter of 2.46 nm, and a pore volume of 0.248 cm3 g−1. Furthermore, the SEM picture provided visual evidence supporting the observed morphological characteristics of the graphitic structure. The infrared spectra for all samples are recorded and exhibit identical vibration bands. The FTIR analysis allows for the verification of the comparison of functional groups at various pyrolysis temperatures. The optimized sample, designated as WGC-650, had exceptional specific capacitance (CS) characteristics, achieving a value of 198 F g−1 at an applied current density of 1 A g−1 and the capacitance retention is 97% at 3 A g−1 after 1000 cycles. This study shows the potential for producing WGC for energy storage applications due to its straightforward procedure and the use of waste OPF as a valuable resource.